Answer: Jordan worked for 10 hours and Sydney worked for 6 hours.
Step-by-step explanation:
Let x represent the number of hours
that Jordan worked.
Let x represent the number of hours that Sydney worked.
Jordan can iron 20 shirts per hour, and Sydney can iron 25 shirts per hour. They ironed 350 shirts between them. It means that
20x + 25y = 350- - - - - - - - - - - 1
Jordan worked 4 more hours than Sydney. It means that
x = y + 4
Substituting x = y + 4 into equation 1, it becomes
20(y + 4) + 25y = 350
20y + 80 + 25y = 350
20y + 25y = 350 - 80
45y = 270
y = 270/45
y = 6
x = y + 4 = 6 + 4
x = 10
g(x)= 2x-5. Find g(1/2) and g(a)=99.
g(x)=x+5/2. Find g(3), g(0), g(-3) and g(x)=0
Please solve this quickly. I need it right now. No silly answer will not be allowed.
Step-by-step explanation:
i. 3x-1=20
or, 3x= 21
x= 7
ii. 3x+1= 22
3x= 21
x= 7
iii. 2x-5=99
2x= 104
x=52
iv. g(3)= 3+5/2= 11/2
g(0)= 0+ 5/2=5/2
g(-3)= -3+5/2 = -1/2
x+5/2= 0
so, x= -5/2
Answer:
The answer is "5, 12, and 13".
Step-by-step explanation:
Please find the complete question in the attached file.
The right triangle is a triangle with only an angle of 90 degrees, as well as the go in the angle of 90 degrees, which is considered a hypotenuse.
The hypotenuse calculation square is equivalent to both the squared measures of the other two sides:
And even those squares do verify the equation:
So, it's a rectangular (right) triangle, with sides spanning
Answer:
B
Step-by-step explanation:
The elimination method is ideal for solving this system of equations. By which number must you multiply the second equation to eliminate the
yavariable, and what is the solution for this system?
x + 3y - 42
2x-y-14
OA. Multiply the second equation by-3. The solution is x = 12. y - 9.
ов.
Multiply the second equation by-2. The solution is x-12. y = 10.
OC.
Multiply the second equation by 2. The solution is x - 15, y = 9.
OD
Multiply the second equation by 3. The solution is x - 12. = 10.
Reset
Next
Answer:
D. Multiply the second equation by 3. The solution is x = 12, y = 10
Step-by-step explanation:
Given:
x + 3y = 42 (first equation)
2x - y = 14 (second equation)
To solve by elimination, starting with elimination of the y-variable, multiply the second equation by 3 to get a third equation.
2x - y = 14 (2nd eqn.) × 3
6x - 3y = 42 (3rd equation)
Add the 3rd equation and the 1st equation together.
x + 3y = 42 (first equation)
6x - 3y = 42 (3rd equation)
7x = 84
7x/7 = 84/7
x = 12
To find y, substitute x = 12 in the first equation
x + 3y = 42 (first equation)
12 + 3y = 42
12 + 3y - 12 = 42 - 12
3y = 30
3y/3 = 30/3
y = 10
Solution is x = 12, y = 10